Importance of photodynamic therapy in proliferative processes - Nigora F. Abdukhalikova (International Journal of Medical Science and Public Health Research, 2025)
Currently, photodynamic therapy is being introduced into biological research and practical medicine in many countries worldwide. This technology holds great potential for preventive purposes. In our research, we utilized a water-soluble substance known as psoralen, which was isolated from the fig plant (Ficus caricae). This plant is prevalent in the Republic of Uzbekistan. Psoralen was selected as our photosensitizer of choice. To induce proliferative inflammation, we employed a "cotton plate" model. The evaluation of our findings involved analyzing the levels of TGF β1 in the blood and examining any alterations in the structure of mitochondrial membranes of hepatocytes.